Analisa Aliran Daya Sistem Tenaga Pada PT. Trias Sentosa Menggunakan Simulasi - Bahardimas Yanuar Ari Leksono; Misbahul Munir; Novian Patria Uman Putra; Trisna Wati; Nasyith Hananur Rohiem; Ilmiatul Masfufiah (Institut Teknologi Adhi Tama Surabaya, 2022)
A power flow analysis is a study that aims to obtain information on the electrical network system. production development of PT. Trias Sentosa, Tbk. very fast. Especially in the production section, there are always additions and updates to machines, so the burden that is borne will also increase. As a result, in carrying out their duties, the machines will always experience malfunctions or errors. To minimize these conditions, it is necessary to have a power flow analysis in order to review the condition of the electric power system. The benefit of this power flow analysis is that it can determine the condition of an unbalanced load. In research that uses manual calculations and calculations on this ETAP, using the current equation method to get the results of the power flow analysis. case studies of monitored power flow analysis in the form of voltage profiles, output power, input power, transformer loading, power loss values, voltage drop values, and load imbalance values